2020
DOI: 10.1111/clr.13658
|View full text |Cite
|
Sign up to set email alerts
|

Marginal soft tissue recession after lateral guided bone regeneration at implant site: A long‐term study with at least 5 years of loading

Abstract: Background/aim This study evaluated marginal soft tissue recession at implants with simultaneous lateral guided bone regeneration (GBR), at least five years after prosthetic loading. Material and methods Patients treated with GBR at the time of implant placement and adherent to supportive periodontal therapy (SPT) program with at least 5 years of follow‐up were re‐examined in 5 clinical centers. At the last follow‐up, clinical and radiographic data on peri‐implant hard and soft tissue were collected. Multileve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…This varied among studies that reported patient‐level data; Bittner et al (2019) and Cordaro et al (2009) reported frequency values >50%, while four other publications provided frequency values <10% (Cosyn et al, 2011; Lindeboom et al, 2006; S. Raes et al, 2018; and Tian et al, 2019). Among the studies that reported on implant‐level data, one study (Oates et al, 2002) reported an occurrence of >60% of the patients, whereas three other publications (Cairo et al, 2020; Garabetyan et al, 2019; and Malchiodi et al, 2013) reported frequencies <15%. Moreover, the frequency of BSTD was evaluated as a function of the follow‐up time and type of the study and no clear association could be established between these variables (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…This varied among studies that reported patient‐level data; Bittner et al (2019) and Cordaro et al (2009) reported frequency values >50%, while four other publications provided frequency values <10% (Cosyn et al, 2011; Lindeboom et al, 2006; S. Raes et al, 2018; and Tian et al, 2019). Among the studies that reported on implant‐level data, one study (Oates et al, 2002) reported an occurrence of >60% of the patients, whereas three other publications (Cairo et al, 2020; Garabetyan et al, 2019; and Malchiodi et al, 2013) reported frequencies <15%. Moreover, the frequency of BSTD was evaluated as a function of the follow‐up time and type of the study and no clear association could be established between these variables (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] The mucosal level change could be attributed to the surgical procedure, 4 prosthesis transmucosal design, 5 the soft tissue quantity and quality, supporting bone, and the soft tissue configuration over time. 6,7 Among these, the prosthesis contour design appears to significantly affect the shape of peri-implant soft tissue. 8,9 In the ninth edition of the Glossary of Prosthodontic Terms, the emergence profile was defined as "the contour of a tooth or restoration, such as the crown on a natural tooth, dental implant, or dental implant abutment, as it relates to the emergence from circumscribed soft tissues".…”
Section: Introductionmentioning
confidence: 99%
“…Postsurgical mucosal recession always occurs within 6–12 months after restoration placement and remains relatively stable after that 1–3 . The mucosal level change could be attributed to the surgical procedure, 4 prosthesis transmucosal design, 5 the soft tissue quantity and quality, supporting bone, and the soft tissue configuration over time 6,7 . Among these, the prosthesis contour design appears to significantly affect the shape of peri‐implant soft tissue 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the fixture abutment connection remains also a key factor [2]. It has been described how many elements could affect this critical area, such as fixture and abutment material, surface microtopography, treatments and connection type [8][9][10]. The latter could influence the biological response of peri-implant hard and soft tissues.…”
Section: Introductionmentioning
confidence: 99%